BUILDING DEMOCRACY: TRANSITION AND CONSOLIDATION PATTERNS IN POST-COMMUNIST ROMANIA - Iulia ANGHEL (Studia Universitatis Babeș-Bolyai. Philosophia, 2015)
The study intends to analyse patterns of transition and consolidation connected to Romanian scenario, in order to identify the vulnerabilities and dysfunctionalities derived from local trajectory towards democratization. The research is grounded on two major assumptions. First work hypothesis claims the existence of a strong particularism within Romanian rite of separation, entailing also significant differences in sphere of consolidation prospects, while second hypothesis sustains the conservation of societal modernization gaps, influencing the ascent to democratization. Exploratory endeavour utilize a comparative frame, decrypting the transitional mechanism trough filter of four regime change theories: functional approach, transnational view, genetic theory and interactive paradigm.